Effect of topical ketorolac tromethamine and topical nepafenac on maintaining pupillary dilation during phacoemulsification - Richard Atanis, MD; Prospero Ma. Tuano, MD; Jay Vicencio, MD; Jose Ma. Martinez, MD; Lee Verzosa, MD (Philippine Journal of Ophthalmology)
Objective: This study compared the effectiveness of prophylactic administration of topical ketorolac tromethamine 0.5% and nepafenac 0.1% on maintaining mydriasis during phacomulsification.